A time of angels - Hesse, Karen (New York : Hyperion Books for Children, 1995)
Sick with influenza during the 1918 epidemic and separated from her two sisters, a young Jewish girl living in Boston relies on the help of an old German man, and her visions of angels, to get better and to reunite herself with her family.
Keywords: Influenza; Sisters; Angels; Jews -- United States